An Impact Assessment of National Health Insurance Scheme (NHIS) On Employees’ Productivity in Adamawa State, Nigeria - Pariya Umar Aisha; Nasiru A. Umar (Yayasan Riset dan Pengembangan Intelektual, 2021)
This study assessed the impact of the National Health Insurance Scheme (NHIS) on employee productivity. The study utilized data from the Federal College of Education (FCE, Yola) and American University of Nigeria (AUN) using a structured questionnaire. A sample of 200respondents was drawn from the two institutions. Count data models were used to examine the effects of the benefits offered by NHIS on the productivity of workers. The findings from this study reveals that awareness and prevention campaign, drug quality, health treatment and dental care service reduce the probability of a worker falling sick and missing work days. The result shows 61% of workers who are insured have never missed work due to sickness in the last 12 months. The study recommends that, the services offered by the NHIS should be more strengthened and sustained since they are found to be impacting much on workers. Thus, proper monitoring and supervision of the programme are important to ensure that the goal of the scheme is attained. Awareness and prevention campaigns should be conducted at regular intervals to bridge the information asymmetric among individuals. When workers are enlightened and informed about certain diseases, for example, diabetes, blood pressure, cancer, etc. They will be able to take both preventive and curative measures. Health treatment should also be improved at the various healthcare centers enrolled in NHIS scheme to ensure that there is efficiency and effectiveness in the treatment given to the beneficiaries. Keywords: Productivity, Health Insurance, NHIS